PELAKSANAAN PENGELOLAAN INSTALASI PENGOLAHAN LUMPUR TINJA (IPLT ) PADA DINAS LINGKUNGAN HIDUP KOTA PADANG - Yola Oktavia; dra.gusnayetti gusnayetti (LPPM STISIP IMAM BONJOL, 2026)
The Septage Treatment Plant, commonly known as IPLT, is specifically designed to treat fecal sludge to ensure it does not pose a hazard to public health or the surrounding environment.This facility is engineered to accommodate the total volume of fecal sludge generated by the residents within a specific administrative area. The approach utilized in this study is a qualitative approach. Specifically, the researcher employed a descriptive qualitative research type, which aims to examine existing problems and the applicable standard operating procedures within the facility. The research was conducted at the Padang City Septage Treatment Plant (IPLT), located on Jalan Belakang Kompi Bantuan, Surau Gadang Village, Nanggalo District, Padang City, West Sumatra.The research focus serves as the primary object or the central point of attention in this study. The focus of this research is categorized into two main aspects: 1) The implementation of septage management at the Padang City Environmental Service; and 2) The comprehensive processes of planning, organizing, implementing, and supervising the IPLT operations in Padang City.The data analysis technique applied in this study is descriptive data analysis based on the Miles and Huberman model (1992:15,20). This involves an interactive model consisting of several stages: data collection, data reduction, data display, and conclusion drawing. The research findings indicate that the Padang City IPLT continues to operate effectively to this day. Its operations align with the predetermined planning to achieve the strategic objective of becoming a source of Regional Original Revenue (PAD) while consistently serving the entire region of Padang City.